Public Health Strategies for Early Myopia Detection and Intervention in U.S. School Settings - Javaid , Gjergj Ruci (Journal of Educational Research and Policies, 2026)
Myopia is becoming a growing concern among school-aged children in the United States, posing risks to academic performance, social development, and long-term visual health. This narrative review examines myopia prevalence, emphasizing the role of school-based screening and intervention programs. It discusses current public health strategies, including technology-driven screening, mobile clinics, and educational campaigns. Despite these advancements, financial limitations, workforce shortages, and unequal access remain significant barriers. The review recommends standardizing screening protocols, expanding funding, integrating myopia education in school curricula, and fostering community partnerships. A collaborative approach involving policymakers, educators, and eye care professionals is essential to ensure equitable access to myopia care for all children.